Primary gastric melanoma in an Asian patient: a rare case report of early detection and therapeutic uncertainty - Binh V. Pham; Nam H. Ha; Van T. Ta; Hoa T.T. Nguyen (International Journal of Surgery Case Reports, 2026)
Introduction and importance: Primary gastric melanoma (PGM) is an exceedingly rare malignancy, especially in Asian populations, that presents major diagnostic and therapeutic dilemmas. Presentation of the case: We report the case of a 53-year-old Vietnamese man who presented with only vague epigastric discomfort. During a routine esophagogastroduodenoscopy, a small pigmented lesion was incidentally discovered in the stomach. An initial biopsy confirmed the presence of malignant melanoma, supported by immunohistochemical positivity for SOX10. A subsequent comprehensive workup – including dermatological and ophthalmological evaluations and comprehensive systemic imaging – found no other primary melanocytic sites, thereby fulfilling three of Blecker’s criteria. A total laparoscopic gastrectomy with D2 lymphadenectomy was performed. Postoperative histopathology showed no residual tumor in the gastric specimen or in any of the lymph nodes examined. Clinical discussion: The absence of established treatment standards for PGM necessitated a complex multidisciplinary discussion. Key questions centered on balancing oncologic radicality (total gastrectomy, D2 lymphadenectomy) with patient quality of life, especially given the likelihood of complete excision at the time of the initial biopsy. The finding of no residual disease post-resection complicated the indication for adjuvant systemic therapy. The diagnosis was supported by SOX10 staining and the fulfillment of Blecker’s criteria (pending completion of the 6-month surveillance period). The upfront radical approach, though potentially excessive, preempted the need for a second operation to confirm pathological clearance. Conclusion: This report contributes to the limited literature on PGM, highlighting the importance of early detection, multidisciplinary discussion, and long-term follow-up in such rare presentations.